A Baby at All Costs? Exploring the Use and Provision of Unproven Adjuvant Treatments in the Context of IVF - Jones, Georgina L.; Lang, Victoria; Hudson, Nicky (Seminars in Reproductive Medicine, 2021)
The year 2018 marked 40 years since the birth of Louise Brown, the first baby born as a result of pioneering in vitro fertilization (IVF) treatment. Since then, advances have seen a wide range of reproductive technologies emerge into clinical practice, including adjuvant treatments often referred to as IVF “add-ons.” However, these “optional extras” have faced growing criticism, especially when they have often come at additional financial cost to the patient and have little evidence supporting their efficacy to improve pregnancy or birth rates. Despite this, according to the latest national patient survey by the Human Fertilisation and Embryology Authority, three quarters of patients who had fertility treatment in the United Kingdom in the past two years had at least one type of treatment add-on highlighting the growing demand for these interventions. This article uses a psychosocial perspective to consider the motivations behind patient and clinician behavior along with the wider societal and economic factors that may be impacting upon the increase in the use of adjuvant treatments in fertility clinics more widely. It suggests the reasons fertility patients use unproven “optional extras” are complex, with interpersonal, psychological, and social factors intertwining to generate an increase in the use of IVF add-ons.
Keywords: adjuvant treatments; in vitro fertilization; infertility; add-ons; psychosocial